ORGANIZATIONAL COMMITMENT, EMPLOYEES PERFORMANCE AND ISLAMIC WORK ETHICS: HALAL RESTAURANT PERSPECTIVE - Zainuddin S; Erwin Jafar; Muhammad Nur Alam Muhajir; Muhammad Rusli (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
Halal restaurants are a staple for Muslims. Employee performance is an important element in increasing the number of visitors to halal restaurants. This study aims to analyze the effect of Islamic work ethic on employee performance, the effect of Islamic work ethic on organizational commitment; and the effect of organizational commitment on employee performance. This study uses a type of quantitative research. The population in this study is all halal restaurant employees who have halal certification in Indonesia. Sampling using purposive sampling with certain criteria. Data collection techniques using a questionnaire. While the data analysis of this study uses SEM PLS.The results of this study indicate that the Islamic work ethic variable has an influence on employee performance, Islamic work ethic has a positive effect on the dimensions of organizational commitment. In addition, the results of this study indicate that organizational commitment variables affect employee performance. This research has two contributions, namely empirical and policy aspects. The results of this study are additional literature related to empirical evidence of the influence of Islamic work ethics and organizational commitment to halal restaurants. In addition, the results of this study help halal restaurants in sustainable development.